2023
DOI: 10.3390/molecules28031093
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and GC-MS Profile of Cardamom (Elettaria cardamomum) Essential Oil Obtained by a Combined Extraction Method—Instant Controlled Pressure Drop Technology Coupled with Sonication

Abstract: Cardamom Essential oils are highly demanded because of their antimicrobial, anti-inflammatory, and antioxidant activities. Nonetheless, retrieving quality extracts quickly with efficient energy savings has been challenging. Therefore, green technologies are emerging as possible alternatives. Thus, this study evaluates the yield and quality of the instant controlled pressure drop (DIC) process coupled with ultrasound-assisted extraction (UAE) of cardamom essential oil (CEO). Likewise, the antioxidant activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…GC–MS analysis revealed the highest constituent, with limonene comprising 76.9 % of the oil. The recovery of EOs from the seeds of cardamom by the UAE coupled with ICPDT has been documented by Castillo et al [53] . Thirteen different conditions were applied, leading to various extraction yields.…”
Section: Ultrasound-assisted Extraction (Uae) Of Eosmentioning
confidence: 85%
See 1 more Smart Citation
“…GC–MS analysis revealed the highest constituent, with limonene comprising 76.9 % of the oil. The recovery of EOs from the seeds of cardamom by the UAE coupled with ICPDT has been documented by Castillo et al [53] . Thirteen different conditions were applied, leading to various extraction yields.…”
Section: Ultrasound-assisted Extraction (Uae) Of Eosmentioning
confidence: 85%
“…In the cosmetics industry, EOs play a role as fragrance components in perfumes, contribute to aromatherapy in skincare, and are incorporated into various products such as lip balms, massage oils, skincare products, and hair care products. EOs' versatility makes them valuable in these sectors, adding a wide range of flavor, aroma, and therapeutic properties to products [6] , [53] . Fig.…”
Section: Essential Oils (Eos)mentioning
confidence: 99%
“…Several studies have characterized the nonvolatile, volatile, and fatty oil components in plants by GC–MS and UPLC–MS/MS, accompanied by antioxidant activities of components in plants (Ali et al., 2022 ; Al‐Nemari et al., 2020 ; Castillo et al., 2023 ; Duan et al., 2022 ; Hefny Gad et al., 2021 ). A previous study demonstrated that phenolic acids, represented by chlorogenic acid and caffeic acid, are the main reason for the antioxidant effect of ESF (Kim et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Color was analyzed with a colorimeter based on CIE-Lab* coordinates (CIELAB; L* coordinate for luminosity, 0 for black and 100 for white; a* coordinate for green/red; b* coordinate for blue/yellow), taking measurements at three random points on each CD (n = 6) (Castillo et al, 2023).…”
Section: Color Determinationmentioning
confidence: 99%